SIFAT ORGANOLEPTIK KEFIR SUSU KAMBING PERANAKAN ETAWA: PENGARUH LEVEL GRANULA KEFIR KOMERSIAL DAN SUKROS - Purwaningsih; Titiek F. Djaafar; Tri Marwati (AGROISTA : Jurnal Agroteknologi, 2019)
Goat's milk has a complete nutritional content, but so far it has not been favored because of goaty flavor which comes from short and medium chain fatty acids such as caproic acid, caprylic acid and capric acid. Processing milk into fermented milk like kefir is one method of processing milk that is useful to increase the nutritional value of milk and eliminate goaty flavor. The aim of this study is to know the effect of the use of kefir granule and sucrose levels on the sensory properties of PE goat’s milk kefir. The ingredients used are PE goat's milk, kefir granules, sucrose, aquadest. The Completely Randomized Design with six treatments is used in this study. Organoleptic test were using a hedonic scale. The treatments were arranged as follows: A1B1 (5% kefir granules 5%, 0% sucrose); A1B2 (5% kefir granules, 5% sucrose); A1B3 (5% kefir granules, 10% sucrose); A2B1 (10% kefir granules, 0% sucrose; A2B2 (10% kefir granules, 5% sucrose) and A2B3 (10% kefir granules, 10% sucrose). The results of this study indicate that the treatment of kefir granules (5 and 10%) and sucrose (0.5, and 10%) have a significant effect on aroma, thickness, taste and overall acceptance, but not significantly different of color. The use of 5% kefir granule and sucrose 10 % levels (A1B3) is the preferred kefir. Keywords: Kefir granules, sucrose, sensory properties, suc